The bone garden : [compact disc, unabridged] a novel : - Gerritsen, Tess (Random House Audio, 2007)
Present day: Julia Hamill has made a horrifying discovery on the grounds of her new home in rural Massachusetts: a skull buried in the rocky soil--human, female, and, according to the trained eye of Boston medical examiner Maura Isles, scarred with the unmistakable marks of murder. Boston, 1830: In order to pay for his education, medical student Norris Marshall has joined the ranks of local "resurrectionists"--those who plunder graveyards and harvest the dead for sale on the black market. But when a distinguished doctor is found murdered and mutilated on university grounds, Norris finds that trafficking in the illicit cadaver trade has made him a prime suspect.